The Affective Nexus: Weaving Individual Behavior and Organizational Culture in an Indonesian Islamic Boarding School - Damayanti, Ripa; Hakim, Lukman; Jamrizal, Jamrizal (HEUTAGOGIA: Journal of Islamic Education, 2025)
This study investigates the intricate dynamics between individual behavior and organizational culture within the context of Islamic boarding school education. The primary aim is to explore the foundations of student motivation, the perception of the organizational climate, and the influence of emotion on the learning environment. This research employed a qualitative case study design at Aswaja Bungo Pesantren in Jambi, Indonesia. Data were gathered over two months through participant observation, semi-structured interviews with fifteen purposively selected teachers (ustadz), staff, and students (santri), and analysis of institutional documents. Thematic analysis, guided by the interactive model of Miles, Huberman, and Saldaña, was utilized to interpret the data. The findings reveal that student learning motivation is driven principally by non-material recognition from teachers and the contextual relevance of the curriculum, rather than by material rewards. A supportive organizational climate, characterized by informal and empathetic teacher-student interactions, was found to be fundamental in establishing psychological safety. Furthermore, the study identifies a strong correlation between teachers' positive emotional expressions and the collective classroom mood, which directly enhances student engagement and participation. A secondary finding indicates that teacher job satisfaction, fostered by institutional appreciation, positively influences the quality of their pedagogical interactions. This research underscores that affective and relational dynamics are not peripheral but central to the educational process in religious boarding schools. The study's implications suggest a need for educational leaders to integrate emotional pedagogy into teacher training and institutional strategies. This research is limited by its single-site design; therefore, caution is advised in generalizing the findings. Future research is recommended, utilizing longitudinal or comparative mixed-methods approaches to validate these insights across diverse institutional contexts.